2021
DOI: 10.1108/ijpsm-11-2019-0289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of demographic, political and financial factors on municipal transparency: a dynamic panel approach

Abstract: PurposeThis paper seeks to identify some of the most important drivers of Portuguese local government transparency in their activities over time. The recent literature on good governance has repeatedly identified transparency as central to promoting accountability, preventing corruption and mismanagement and stimulating greater civic engagement. As local government is the main provider of many primary services to the population, evaluating its transparency is especially relevant given that misconduct or maladm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 59 publications
1
14
0
1
Order By: Relevance
“…In fact, they show a nonsignificant relationship between POPDENS and PAFRQ. This result, although unexpected, confirms what was found by Navarro‐Galera et al (2018) and Brás and Dowley (2021).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In fact, they show a nonsignificant relationship between POPDENS and PAFRQ. This result, although unexpected, confirms what was found by Navarro‐Galera et al (2018) and Brás and Dowley (2021).…”
Section: Resultssupporting
confidence: 91%
“…In this regard, some studies have found that population density is associated with greater public local transparency (Alcaraz-Quiles et al, 2014;Homsy & Warner, 2015;Lowatcharin & Menifield, 2015;Ortiz-Rodríguez et al, 2018), while other studies have found a negative relationship (Gesuele & Metallo, 2017). Other studies have instead found a nonsignificant association between the population density and the transparency of local governments (Brás & Dowley, 2021;Navarro-Galera et al, 2018). From a theoretical standpoint, according to agency and legitimacy theories, local governments have a greater incentive to legitimize their actions and reduce information asymmetries in presence of a greater population density that requires specific information needs regarding public choices (Alcaraz-Quiles et al, 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A final remark could be dedicated to the participation tools. As seen in 17% of LGs analysed, a fundamental way of improving participation is to use ICT technologies that promote citizens' active involvement and strengthen accountability and transparency, which is essential for this type of PA (Brás and Dowley, 2021). However, in 51% of LGs, collaboration is also stimulated by public meetings and workshops, where people can freely discuss projects.…”
Section: Discussionmentioning
confidence: 99%